EXPLORING "SCIENTIFIC APPROACH" IN ENGLISH LANGUAGE TEACHING - Suharyadi, Suharyadi (2013)
Inthisyear(2013)theMinistryofEducationandCulturehasjustlaunchedanewcurriculumforelementaryandhighschoolsCurriculum2013.ThiscurriculumisclaimedtobedifferentfromthepreviousoneKTSP-inseveralaspects.Oneofthedifferencesisthatascientificapproachisintroduced.Thisapproachisoldandnew.Itisoldasithasbeenusedinscience.ItisnewbecauseitisnewlyappliedinEnglishlanguageteaching(ELT).Forlanguageteachers(English)thisapproachisnotclearyetandprobablyitcausessomecontroversies.ThispaperaimsatexploringthenotionsofscientificapproachanditspossibleapplicationinEnglishlanguageteaching.KeyWordsScientificApproachEnglishLanguageTeaching.